PROCESSESS OF CHILDREN’S LEARNING AND SPEECH DEVELOPMENT IN EARLY YEARS - Undiyaundeye, Florence A; A, Basake Julius (PEOPLE: International Journal of Social Sciences, 2018)
Speech development is important children's development. a crucial tool to learning for communication and building relationship with others as well as enhancing language attainment in children which is top priority. It is not only the sole responsibility of those working with children to provide support for language development and sustenance of the child but a joint partnership with parents, caregiver, families and policymakers. Many parents begin communication with children once pregnancy is established in a woman and the voices of other people who communicate with this woman make contact with the baby. At early childhood stages babies cry to attract attention and communicate with adults to get what is their need. This cuts across when they are wet, hungry, in pain, need attention and adults in turn respond positively to the babies. From when children are delivered, they get integrated in the language of the day by those who interact with them as parents and other adults. They respond through meeting with eyes, making sounds and gurgling. This led the children through taking part in conversations and become communicators. The development of language is a strong bridge for a child’s brain and cognitive development. When there exist many options of language to choose from, ingenuity of language usage abound and new ways of talking is generated. The creation of verbal communication cannot be viewed independently but hugely important to an all round development during the first years of his or her life.